2008
DOI: 10.1021/cm800167x
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Photocatalytic Properties of Transparent 12 Tungsto(VI) Phosphoric Acid−TiO2 Hybrid Films

Abstract: Using the layer-by-layer method, 12 tungsto(VI) phosphoric acid (PW12) and TiO2 hybrid thin films were prepared. In 2-propanol decomposition, two-bilayer thin films (ca. 15 nm) showed more rapid decomposition than control TiO2 and PW12 films under both UV and visible light illumination. Visible light illumination was required for continuous 2-propanol decomposition. Photocatalytic decomposition activity depends on the number of bilayer coatings, the top coating, and the organic compounds for decomposition. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 32 publications
1
25
0
1
Order By: Relevance
“…Nanoparticles at a diameter of 50 nm are evident in the PSS/TiO 2 LbL film. The size of the nanoparticles in the AFM image is larger than the actual size of the TiO 2 nanoparticles (5-7 nm), [22] probably because the curvature radius of the AFM probes is large (ten to twenty nanometers). The height difference between the PSS/TiO 2 layers and the Si wafer is 15-17 nm, which indicates that the thickness of the PSS films is less than 3 nm.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Nanoparticles at a diameter of 50 nm are evident in the PSS/TiO 2 LbL film. The size of the nanoparticles in the AFM image is larger than the actual size of the TiO 2 nanoparticles (5-7 nm), [22] probably because the curvature radius of the AFM probes is large (ten to twenty nanometers). The height difference between the PSS/TiO 2 layers and the Si wafer is 15-17 nm, which indicates that the thickness of the PSS films is less than 3 nm.…”
Section: Resultsmentioning
confidence: 92%
“…[20,21] Yanagida et al, have reported a technique of the fabrication of layer-by-layer (LbL) films consisting of anionic polymers and TiO 2 nanoparticles with precise control of the film thickness. [22] Using electroless deposition, metal films are formed selectively on the region where noble metal nanoparticles are deposited. [23,24] We have reported the fabrication methods of functional nanomaterial films on plastic sheets from the viewpoints of increasing operating lifetime of emitting layers and of reducing material consumption and fabrication steps.…”
Section: Introductionmentioning
confidence: 99%
“…24) Reference samples, (TiO 2 ) n and (PW 12 ) n were also prepared via photocatalytic decomposition of the polyelectrolytes in LBL films of [poly(styrenesulfonate)/TiO 2 ] n and [poly(diallyldimethylammonium)/ Yanagida: Nano/microsized TiO 2 composite photocatalysts for environmental purification PW 12 ] n , respectively. 23) Photocatalytic activities of the composites were examined using gaseous 2-propanol. Figure 3(a) portrays the change in the concentration of 2-propanol during UV illumination for the n = 2 films.…”
Section: Introductionmentioning
confidence: 99%
“…POMs have been used to construct the self-assembly films as anions via the LbL method [32][33][34][35]. To our best knowledge, few reports have focused on the photocatalytic properties of POM-containing composite films [36][37][38]. However, the research on preparing functional POM-containing composite films still attracts substantial interest.…”
Section: Introductionmentioning
confidence: 99%